ASSESSING FACTORS INFLUENCING VACCINE HESITANCY AMONG PREGNANT FEMALES A QUALITATIVE RESEARCH IN OBSTETRIC AND GYNECOLOGY OPD IN NISHTAR HOSPITAL MULTAN - DILDAR , N; NISA , QU; NAZIR , S; PERVEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Vaccine hesitancy is a significant public health challenge, particularly in low- and middle-income countries like Pakistan. Pregnant women are a high-priority group for immunization due to their increased vulnerability to infectious diseases and the benefits of passive immunity for newborns. Despite these advantages, vaccine uptake among pregnant women in Pakistan remains suboptimal, influenced by various cultural, social, and healthcare-related factors. Objective: To explore the factors contributing to vaccine hesitancy among pregnant women attending the Obstetrics and Gynecology OPD at Nishtar Hospital, Multan. Methods: This qualitative study involved 35 pregnant women recruited through purposive sampling. Data were collected using semi-structured interviews and focus group discussions conducted in a private setting within the hospital. Thematic analysis was performed using NVivo software to identify barriers to vaccination, including perceptions of vaccine safety, cultural influences, and healthcare accessibility. Results: The study revealed that 71.4% of participants feared vaccine side effects, and 57.1% doubted vaccine efficacy. Social and cultural factors, such as religious beliefs (34.3%) and family influence (28.6%), significantly impacted vaccination decisions. Additionally, accessibility barriers, including long distances to vaccination centers (42.9%) and inadequate healthcare counseling (57.1%), further contributed to vaccine hesitancy. These findings align with previous studies in similar settings, emphasizing the need for targeted educational interventions. Conclusion: Vaccine hesitancy among pregnant women in Pakistan is driven by fears of side effects, cultural influences, and systemic healthcare barriers. Addressing these challenges through improved healthcare provider communication, targeted education, and enhanced accessibility to vaccination services is critical for improving maternal and neonatal health outcomes.